Increasing Teacher Innovation To Support 21st Century Learning - Oding Sunardi; Sri Setyaningsih; Syairi Anwar (Universitas Pakuan, 2023)
This study aims to identify effective strategies for enhancing teacher innovation in the context of 21st-century learning by examining the mediating influence of technological literacy and the direct impact of reading culture. Employing a mixed-methods approach that integrates quantitative and qualitative techniques with path analysis, the research was conducted from April to August 2023 in Depok City, Indonesia, involving 231 elementary school teachers selected through proportional random sampling from a total population of 1,740 teachers. The findings reveal that a strong reading culture significantly contributes to fostering teacher innovation (path coefficient = 0.316), while technological literacy also exerts a positive direct effect on innovation (path coefficient = 0.084). Additionally, reading culture positively influences technological literacy (path coefficient = 0.750), indicating that literacy development enhances teachers’ capacity to integrate technology effectively into their pedagogical practices. The study concludes that building a robust reading culture and improving technological literacy are key drivers for cultivating innovative teaching behaviors aligned with the demands of 21st-century education, where creativity, adaptability, and digital competence are critical for professional growth and instructional transformation.